PENGARUH SISTEM AKUNTANSI KEUANGAN DAERAH, AKSESIBILITAS LAPORAN KEUANGAN, DAN PENGENDALIAN INTERNAL TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH - Zeny Antika; Yunika Murdayanti; Hafifah Nasution (Fakultas Ekonomi, Universitas Negeri Jakarta, 2020)
This study aims to examine the effect of the regional financial accounting system, the accessibility of financial reports and internal controls on the accountability of regional financial management. This research is a quantitative research. The population in this study is the whole part involved in the management of regional finances in the villages in Bekasi City. The sampling technique uses simple random sampling. Data collection techniques used in this study using survey methods. The data used are primary data in the form of questionnaires distributed to respondents. The analytical method used is multiple regression analysis with SPSS (Statistical Product and Services Solution) version 26. Based on the results of the study showed that the regional financial accounting system, the accessibility of financial statements, and internal control have a significant positive effect on the Financial Accountability Of Local Government.